Comprehensive analysis of the 5-HTTLPR allelic polymorphism effect on behavioral and neurophysiological indicators of executive control in people from different ethnic groups in Siberia - A. N. Savostyanov; D. V. Bazovkina; S. A. Lashin; S. S. Tamozhnikov; A. E. Saprygin; T. N. Astakhova; U. N. Kavai-ool; N. V. Borisova; A. G. Karpova (Вавиловский журнал генетики и селекции)
The allelic polymorphism of the serotonin transporter’s gene 5-HTTLPR is considered as one of the factors determining an individual genetic predisposition to the development of a wide range of affective disorders, including depression. Many studies have shown that the climatic and social conditions of people’s life can have a significant impact on the connections of 5-HTTLPR with the risk of depression. The stop-signal paradigm (SSP) is an experimental method allowing evaluating an individual ability to the self-control of behavior in a changing environment. In the SSP experiment, a subject should either press one of several buttons quickly after the appearance of the target stimuli or suppress the already started movement if an inhibitory signal follows the target stimulus. The aim of this study is a research of associations between the allelic the 5-HTTLPR polymorphism and the individual scores of the personal anxiety level, as well as the behavioral and neurophysiological indicators of the ability to self-control over motor reactions in the SSP. The study was conducted among people from three ethno-regional groups: healthy Caucasoids from Novosibirsk, the Mongoloid groups of the indigenous population of the Tuva Republic and Sakha Republic (Yakutia). Genetic, ethnographic, and psychological influences on an individual’s ability to control motor responses were compared. The amplitude of the premotor peak of the evoked brain potential was used as a neurophysiological marker of the person’s readiness to the execution of target-directed activity. It was revealed that the frequency of the S-allele polymorphism 5-HTTLPR was significantly higher for both mongoloid groups compared to the Caucasoids. The S/S genotype was associated with an increased level of personal anxiety and at the same time with a better ability to the self-control of behavior in the SSP experiment. Anxiety level, participants’ sex, ethnicity, and allelic polymorphism 5-HTTLPR had a statistically significant effect on the amplitude of the premotor readiness potential recorded under the SSP conditions in the frontal and parietal-occipital cortical regions. Our data support the hypothesis that the S/S genotype of the 5-HTTLPR polymorphism may be associated with more success in adapting to the climatic conditions connected with high life risk in comparison to L/L and L/S genotypes.